PENGARUH KOMITMEN KERJA, DISIPLIN KERJA, DAN BUDAYA ORGANISASI TERHADAP PRESTASI KERJA GURU UPT SD NEGERI SIDOREJO 1 DAN UPT SD NEGERI SIDOREJO 2 KECAMATAN TUBAN KABUPATEN TUBAN - Tutik Sriwahyuni; Ahmad Thohirin; Suyitno Suyitno (STKIP Pesisir Selatan, 2026)
Objective: Teacher work performance is one of the essential determinants of educational quality and institutional effectiveness, particularly in achieving learning outcomes and supporting the implementation of educational quality assurance. This study aimed to examine the effects of work commitment, work discipline, and organizational culture on teachers' work performance, both partially and simultaneously, at UPT SD Negeri Sidorejo 1 and UPT SD Negeri Sidorejo 2, Tuban District, Tuban Regency. Methods: This study employed a quantitative explanatory research design. The population consisted of all teachers from both schools, totaling 50 respondents. Since the population was relatively small, saturated sampling was applied so that all teachers became research respondents. Data were collected using structured questionnaires and analyzed through multiple linear regression after passing validity, reliability, and classical assumption tests. Results: The findings revealed that work commitment had a positive and significant effect on teacher work performance with an effective contribution of 23.6%. Work discipline also positively and significantly influenced teacher work performance